THE USE OF FLUOROSCOPY IN THE REMOVAL OF FOREIGN BODIES FROM MAXILLOFACIAL REGION: Removal of Foreign Bodies from Maxillofacial Region - Khan, Idrees; Bukhari, Syed Gulzar Ali; Ahmed, Waseem (Pakistan Armed Forces Medical Journal, 2009)
INRODUCTION Foreign bodies are now more frequently found in maxillofacial tissues due to firearm injuries associated with emerging terrorism and evolving explosive devices in South Asia and especially in tribal areas of Pakistan. Oral and maxillofacial surgeons are frequently facing such situations in which advanced imaging technologies like computerized tomogram (CT), magnetic resonance imaging (MRI) are not available. Despite of the preoperative localization of foreign bodies through radiographs. Intraoperative guidance, when navigating through the delicate tissues is very important to avoid damage to these delicate structures, decrease operating time in terms of intraoperative localization and retrieval of foreign bodies [1]. Fluoroscopy is ubiquitous and is used frequently for removal of foreign bodies from upper aerodigestive tract [2, 3]. Fluoroscopy is more reliable, offers real time imaging, with precise intraoperative localization of foreign body and easily available [4]. Without prior localization of the foreign body surgery may do harm rather than giving benefit to the patient.